2019
DOI: 10.1016/j.psyneuen.2019.01.015
|View full text |Cite
|
Sign up to set email alerts
|

Successful aging, cognitive function, socioeconomic status, and leukocyte telomere length

Abstract: Successful aging mediated the association between chronological age and telomere length  Lower socioeconomic status was associated with larger age-related decreases in telomere length  The cognitive functioning dimension of successful aging was uniquely related to telomere length

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0
3

Year Published

2020
2020
2021
2021

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 51 publications
0
10
0
3
Order By: Relevance
“…This is a result of modifications in socio-environmental and biological factors during the human life course [2], with recent studies suggesting that some diets, economic status, the presence of a caregiver, are correlated with better aging [2][3][4][5][6]. Genetic signatures that predict the phenotypic outcome of exceptional long-living individuals are also identified [5,6].…”
Section: Introductionmentioning
confidence: 99%
“…This is a result of modifications in socio-environmental and biological factors during the human life course [2], with recent studies suggesting that some diets, economic status, the presence of a caregiver, are correlated with better aging [2][3][4][5][6]. Genetic signatures that predict the phenotypic outcome of exceptional long-living individuals are also identified [5,6].…”
Section: Introductionmentioning
confidence: 99%
“…Greater longevity is often linked with more years spent in a vulnerable period 2 . There is a significant variation, however, in the rate of deterioration in physical and cognitive functioning in older adults 3 . As a result of deterioration, ageing brings about a range of chronic conditions.…”
Section: Introductionmentioning
confidence: 99%
“…However, no further differences in other cognitive domains were found. One possible explanation is that not all domains are affected by SES-related factors; several studies focused on the effect of SES on cognition during aging, which measured cognitive functions using MMSE [45,46]. One of these studies found that higher SES can act as a protector factor of age-related decline in cognitive function; the second study found that cognitive impairments in the elderly are independent of SES status.…”
Section: Ses Effects On Cognitive Performancementioning
confidence: 99%